2023
DOI: 10.3390/su15065536
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Scheduling Optimization for Container Handling by Using Driverless Electric Truck in Automated Container Terminal

Abstract: With the increasing maturity of automatic driving technology, the commercial value of driverless container trucks has been gradually excavated. Compared with social roads, the internal roads in the port area have certain practicing advantages. By taking into account the operational characteristics of the driverless electric container truck and the coordination of quay and yard cranes, this paper aims to explore the configuration and optimized scheduling model of the driverless electric container truck with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the establishment of road widths for open-pit mines, one must consider the maximum widths of the diverse types of mining trucks utilized in the mine, the minimum lateral safety distance when two mining trucks intersect, and the safe width of the mining In the establishment of road widths for open-pit mines, one must consider the maximum widths of the diverse types of mining trucks utilized in the mine, the minimum lateral safety distance when two mining trucks intersect, and the safe width of the mining trucks in relation to the road's edge. Equation (1) displays the conventional road width [11]:…”
Section: Open-pit Mine Road Width Analysismentioning
confidence: 99%
“…In the establishment of road widths for open-pit mines, one must consider the maximum widths of the diverse types of mining trucks utilized in the mine, the minimum lateral safety distance when two mining trucks intersect, and the safe width of the mining In the establishment of road widths for open-pit mines, one must consider the maximum widths of the diverse types of mining trucks utilized in the mine, the minimum lateral safety distance when two mining trucks intersect, and the safe width of the mining trucks in relation to the road's edge. Equation (1) displays the conventional road width [11]:…”
Section: Open-pit Mine Road Width Analysismentioning
confidence: 99%
“…Karam et al [28] incorporated realistic factors, such as internal truck shortages and handling time, into a model integrating berth, QC, and internal truck allocation, achieving energy savings without increasing truck quantity. Hong et al [29] addressed the integrated scheduling problem of dual-trolley QC and driverless electric trucks (DETs) by using a pooling strategy to schedule DETs to meet QC transportation service demand. This achieved a more efficient scheduling scheme with lower energy consumption.…”
Section: Energy Saving and Emission Reduction In Container Terminalmentioning
confidence: 99%
“…Some research has also focused its attention on the relationship between automation in ports and energy consumption [23]. Among them, Hong et al [24] highlighted the advantages of automated electric trucks over manual diesel trucks from a social, economic, and efficiency point of view; in particular, a reduction in total energy consumption is demonstrated. Iris and Lam [25] addressed the integrated energy management and operations planning problem for next-generation green ports; they demonstrated that significant cost savings can be pursued with a smart grid (port micro-grid) with respect to conventional settings.…”
Section: Literature Reviewmentioning
confidence: 99%